Maintenance of Sertoli Cell Number and Function in Immature Human Testicular Tissues Exposed to Platinum-Based Chemotherapy—Implications for Fertility Restoration - Matilionyte, Gabriele; Tharmalingam, Melissa D.; Sanou, Iris; Lopes, Federica; Lane, Sheila; Stukenborg, Jan-Bernd; Spears, Norah; Anderson, Richard A.; Mitchell, Rod T. (Frontiers in Toxicology, 2022)
Background: Retrospective studies in adult survivors of childhood cancer show long-term impacts of exposure to alkylating chemotherapy on future fertility. We recently demonstrated germ cell loss in immature human testicular tissues following exposure to platinum-based chemotherapeutic drugs. This study investigated the effects of platinum-based chemotherapy exposure on the somatic Sertoli cell population in human fetal and pre-pubertal testicular tissues. Methods: Human fetal (n=23; 14-22 gestational weeks) ) testicular tissue pieces were exposed to cisplatin (0.5 or 1.0 μg/ml) or vehicle for 24hrs in vitro and analysed 24-240hrs post- exposure or 12 weeks after xenografting. Human pre-pubertal (n=10; 1-12yrs) testicular tissue pieces were exposed to cisplatin (0.5 μg/ml), carboplatin (5 μg/ml) or vehicle for 24hrs in vitro and analysed 24-240hrs post-exposure; exposure to carboplatin at 10-times the concentration of cisplatin reflects the relative clinical doses given to patients. Immunohistochemistry was performed for SOX9 and anti-Müllerian hormone (AMH) expression and quantification was carried out to assess effects on Sertoli cell number and function respectively. AMH and inhibin B was measured in culture medium collected post-exposure to assess effects on Sertoli cell function. Results: Sertoli cell (SOX9+ve) number was maintained in cisplatin-exposed human fetal testicular tissues (7647±459 vs 7767±498 cells/mm2; p>0.05) at 240hrs post-exposure. No effect on inhibin B (indicator of Sertoli cell function) production was observed at 96hrs after cisplatin (0.5 and 1.0 μg/ml) exposure compared to control (21±5 (0.5 μg/ml cisplatin) vs 23±7 (1.0 μg/ml cisplatin) vs 25±7 (control) ng/ml, p>0.05). Xenografting of cisplatin-exposed (0.5 μg/ml) human fetal testicular tissues had no long-term effect on Sertoli cell number or function (percentage seminiferous area stained for SOX9 and AMH, respectively), compared with non-exposed tissues. Sertoli cell number was maintained in human pre-pubertal testicular tissues following exposure to either 0.5 μg/ml cisplatin (6723±1647 cells/mm2) or 5 μg/ml carboplatin (7502±627 cells/mm2) compared to control (6592±1545 cells/mm2). Conclusions: This study demonstrates maintenance of Sertoli cell number and function in immature human testicular tissues exposed to platinum-based chemotherapeutic agents. The maintenance of a functional Sertoli cell environment following chemotherapy exposure suggests that fertility restoration by SSC transplant may be possible in boys facing platinum-based cancer treatment.